MAPPING THE CREATIVE ECONOMY IN THE PERSPECTIVE OF SMEs EMPOWERMENT IN WEST BANDUNG REGENCY - Siti Fatimah; yuyun Yuniarti; Abdul Rosid (JEES: Journal of Economic Empowerment Strategy, 2021)
SMEs in West Bandung Regency have the potential for both natural resources and human resources. However, there are still many potential sub-sectors in the creative economy in West Bandung Regency that are not utilized, this is due to the unknown location and type of business. The purpose of the study is to describe the Profile and Mapping of the Creative Economy of SMEs in West Bandung Regency. The research method used in this study is a quantitative method using a type of social mapping method. Data collection techniques used are primary data and secondary data. The secondary data used is the Secondary Data Analysis (ADS) approach. Based on the research results, West Bandung Regency has 16 sub-districts with various types of creative economy businesses. Mapping was carried out on 16 creative economy sub-sectors in all sub-districts. Of the total 16 sub-sectors, there are only 14 sub-sectors. Two sub-sectors that are not owned in the West Bandung Regency area are Animation, Film and Video and Advertising Sub-sectors. The largest number of creative economy is the performing arts sub-sector, almost all sub-districts have this sub-sector. The largest performing arts sub-sector is in the Lembang sub-sector with 1369 creative economy business actors or 64% and the least in Gununghalu sub-district as many as 4 creative economy business actors or 1%. The mapping of the creative economy that has been carried out will certainly show that there are business actors in each region that have different sub-sectors, both in the number of business actors and in the number of sub-sectors. So with this the government needs to be able to empowerment the community, especially business actors who have potential to be able to develop. With the efforts made to increase the creativity of business actors, it is hoped that there will be economic growth for both business actors and the development of economic areas in West Bandung Regency